Strategi Peningkatan Pendapatan Petani Salak Desa Macang, Kecamatan Bebandem, Kabupaten Karangasem - WARAPSARI, PUTU TARA ADYUTA; WIDHIANTINI, WIDHIANTINI; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Strategy to Increase Snakefruit Farmers Income in Macang Village,  Bebandem Districts, Karangasem Regency.  Macang Village is one of the villages in Karangasem that has good quality snakefruit, and if it is developed it can increase the income of snakefruit farmers. The purpose of this study was to analyze the socio-economic conditions of snakefruit farmers as well as economic, social, institutional and technological constraints as well as strategies to overcome these obstacles. This type of research uses a combination of qualitative and quantitative, with a non-probability sampling of 25 farmers who are members of the Macang Women Farmer Group. The data analysis technique used in this research is Interpretive Structural Modeling analysis. The strategy that can overcome the socio-economic conditions of snakefruit farmers in Macang Village is to provide information to farmers about good and correct farming methods, provide ideas and innovations in processing snakefruit, as well as economic conditions, namely income by making price agreements, distribution of snackfruit by selling fruit through supermarkets and online sales. The advice given as consideration in this research is to socialize about innovation and marketing of products and technology that can help farmers in running their businesses and overcoming the obstacles they have.